META REVIU: DIVERSITAS TOP MANAGEMENT TEAM TERHADAP KINERJA PERUSAHAAN - Darus Altin; Suhardi Suhardi (JEM Jurnal Ekonomi dan Manajemen, 2021)
The purpose of this literature review is to provide future research opportunities on the diversity of top management teams from the literature of leading management journals, especially in the field of finance and corporate governance from 2015-2018. Two literature review articles previously conducted by Kagzi & Guha, 2018 and Roberson et.al., 2017, became the initial basis for conducting this review literature review. The literature review framework contains the background of the literature review, literature review methodology, and future research opportunities.